STUDY OF FACTORS DETERMINING THE LEVEL OF ACTIVE-DYNAMIC FLEXIBILITY - Pakhrudinova Nigora Yusupovna (Modern American Journals, 2025)
Flexibility is one of the key physical qualities that determines a person's functional capabilities, quality of movement, and level of physical fitness. In today's lifestyle, characterized by high levels of stress, sedentary lifestyles, and prolonged periods of static posture, the ability to maintain sufficient flexibility is especially important. Insufficient flexibility leads to poor posture, chronic back and joint pain, decreased performance, and an increased risk of injury.